Circular business model: an investigation of value stream, barriers, and competitive criteria focusing on Technical Cycles. - Galvão, Graziela Darla Araújo (2021)
Circular economy implies the implementation of clean production and the use of renewable materials through technical cycles. For this, there must be clear and stable policies and tools. This research points out that, despite the growing prominence of Circular Business Models in research and practice, there is still considerable conceptual ambiguity about the drivers and barriers of the concept, the sustainability issues it addresses and the value streams it employs. The thesis is by article and was developed in three parts; Part 1 is an integrative thesis overview, and part 2 is presented the thesis\' papers. The general objective of this thesis is to develop a research model that identifies the role of competitive criteria in technical cycles in the captured value and in the shared value in companies with operation strategies to overcome main barriers or CE obstacles. The thesis applies qualitative and quantitative approaches as this is multi and mixed-methods research. The results suggest that the implementation of technical cycles enhances the competitive criteria of organizations. This thesis contributes to the theory because academic literature on circular economy has expanded, and the discussion on competitive criteria has started, relating them to technical cycles. For practice, presents an algorithm for analysis and strategic conversion of barriers into obstacles, as well these interrelate with each other in the context of Circular Business Model.